The correlation between trait mindfulness and fear of missing out among students who use instagram - Anjani, Nadwa; Deslinda, Gadis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The increasing use of Instagram plays a significant role in connecting its users to other people. However, this convenience has led to the Fear of Missing Out (FoMO) phenomenon. Students who experience FoMO always try to connect to social media and obsessed with the moments around them because of their low trait mindfulness. There is a gap between the results of the previous research and the findings of a preliminary study conducted by researchers on students who use Instagram in Solo Raya. Thus, this study aims to examine the correlation between trait mindfulness and FoMO among students who use Instagram. This research used a quantitative method and applied a correlational approach involving 271 college students who use Instagram in Solo Raya are both male or female aged 18-25. The sampling technique in the study used cluster sampling. The data collection instruments use 2 scales, namely the Trait Mindfulness scale and the FoMO scale. Hypothesis testing was carried out using Pearson product-moment and the rxy result was -0.528 with a significance value of 0.000 (p<0.05). The results showed a negative correlation between trait mindfulness and FoMO. The effective contribution of trait mindfulness to FoMO is 27.9%. The implication of this research is to show the need for strategic efforts such as mindfulness training for college students who use Instagram. This study contributed to reinforcing the literature on similar topics.